2023
DOI: 10.3389/fphys.2023.1174655
|View full text |Cite
|
Sign up to set email alerts
|

General anaesthesia-related complications of gut motility with a focus on cholinergic mechanisms, TRP channels and visceral pain

Abstract: General anesthesia produces multiple side effects. Notably, it temporarily impairs gastrointestinal motility following surgery and causes the so-called postoperative ileus (POI), a multifactorial and complex condition that develops secondary to neuromuscular failure and mainly affects the small intestine. There are currently limited medication options for POI, reflecting a lack of comprehensive understanding of the mechanisms involved in this complex condition. Notably, although acetylcholine is one of the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Another limitation of this method is that smooth muscle function may be affected by anesthesia. It has been found that gastrointestinal motility can be impaired by application of general anesthetics such as isoflurane, via disruption of cholinergic mechanisms 47 , 48 . Care should be taken when determining the manner of anesthesia for future experiments, and consideration as to possible effects of anesthesia on smooth muscle function, and how this may affect results.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this method is that smooth muscle function may be affected by anesthesia. It has been found that gastrointestinal motility can be impaired by application of general anesthetics such as isoflurane, via disruption of cholinergic mechanisms 47 , 48 . Care should be taken when determining the manner of anesthesia for future experiments, and consideration as to possible effects of anesthesia on smooth muscle function, and how this may affect results.…”
Section: Discussionmentioning
confidence: 99%
“…Given their positioning in the gut, these plexi are difficult to access, making monitoring of neural signaling within the ENS challenging. Adding difficulty is the relative inaction of the ENS under general anaesthesia ( 7 ), which results in limited and/or low-amplitude local signaling. These challenges necessitate the construction of a neural recording device that can achieve close proximity to the ENS with a low impedance to maximize signal transduction across the device interface.…”
Section: Main Textmentioning
confidence: 99%
“…As noted above, gut motility is inhibited during general anaesthesia ( 7 ), which has traditionally made acute neural recordings in the ENS a challenge. While our device was able to receive signal from the ENS in response to addition of neural stimulants, large-scale gut motility was largely absent.…”
Section: Main Textmentioning
confidence: 99%
“…Another limitation of this method is that smooth muscle function may be affected by anesthesia. It has been found that gastrointestinal motility can be impaired by application of general anesthetics such as iso urane, via disruption of cholinergic mechanisms 41,42 . Care should be taken when determining the manner of anesthesia for future experiments, and consideration as to possible effects of anesthesia on smooth muscle function, and how this may affect results.…”
Section: And Future Applicationsmentioning
confidence: 99%